Asymmetric synthesis of (S)‐3‐methyleneglutamic acid and its N‐Fmoc derivative via Michael addition–elimination reaction of chiral glycine Ni (II) complex with enol tosylates. Issue 3 (26th December 2020) - Shigeno, Yuhei; Han, Jianlin; Soloshonok, Vadim A.; Moriwaki, Hiroki; Fujiwara, Wataru; Konno, Hiroyuki
Abstract: The use of chiral Ni (II)‐complexes of glycine Schiff bases has recently emerged as a leading methodology for asymmetric synthesis of structurally diverse Tailor‐Made Amino Acids™, playing a key role in the design of modern pharmaceuticals. Here, we report first example of enantioselective preparation of ( S )‐3‐methyleneglutamic acid and its N ‐Fmoc derivative via a new type of Michael addition–elimination reaction between chiral nucleophilic glycine equivalent and enol tosylates. This reaction was found to proceed with excellent yield (91%) and diastereoselectivity (>99/1 de) allowing straightforward asymmetric synthesis of ( S )‐3‐methyleneglutamic acid derivatives and analogues. The observed results bode well for general application of this Ni (II) complex approach for preparation and biological studies of this previously unknown type of Tailor‐Made Amino Acids™ Abstract :